Is there a sexual difference in the relationship between sociodemographic information and the unmet dental care needs of disabled adults? An analysis from a national survey on persons with disabilities - Na-Hyeon Kim; Jae-In Ryu (BMC, 2023)
Abstract Background Health status and health care utilization in people with disabilities are more likely to be poorer than those without disabilities. Previous studies showed that there were gaps in health-related conditions by sociodemographic information and gender but the association between these factors was not explained. This study aims to analyze the relationship between sociodemographic information and the unmet dental care needs of people with disabilities and explore the effect of sex within this relationship. Methods The 2014 national survey on persons with disabilities was used, which separated unmet healthcare needs into medical and dental services. Unweighted samples included 6,824 people with disabilities in total and 6,555 (96.1% of the total, weighted as 6,583) people aged 20 years or older were selected as the study population. Frequency and chi-square tests were conducted to determine differences in the prevalence of unmet dental needs based on socioeconomic information, chronic diseases, and behavioral factors after applying weights. Logistic regressions were performed using an adjusted model with sociodemographic information, chronic diseases, and behavioral variables. All analyses were performed using IBM SPSS Statistics for Windows, version 26 (IBM Corp., Armonk, N.Y., USA). Results Analysis of the sociodemographic factors related to unmet dental care revealed that they were higher in women and the elderly. In the fully adjusted logistic model, most of the sociodemographic information was significantly associated with unmet dental needs. The lowest group was 4.18 times more likely to have unmet dental care needs than the richest group, and females and middle-school graduates were almost twice as likely to experience unmet dental care needs than males and university graduates. Considering the interaction effect of age on unmet dental needs depending on sex differences, the odds ratio decreased for females with every annual increase in both models. Compared with the younger group, the older group showed a lower risk of having unmet dental needs, especially in females. Conclusions The factor most closely related to the unmet dental care needs of disabled people was socioeconomic problems. Its influence also differed by sex and age. Therefore, economic support measures and sexual differences are needed for long-term policy consideration to reduce the unmet dental care needs of disabled people.